2023
DOI: 10.3390/cancers15092469
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Clinicopathologic Profile of Pulmonary Sarcomatoid Carcinoma with Survival Analysis and Genomic Landscape

Abstract: Background: Pulmonary sarcomatoid carcinoma (PSC) is a rare subtype of non-small cell lung cancer (NSCLC) with an aggressive clinical nature and poor prognosis. With novel targeted therapeutics being developed, new ways to effectively treat PSC are emerging. In this study, we analyze demographics, tumor characteristics, treatment modalities, and outcomes of PSC and genetic mutations in PSC. Methods: Data from the Surveillance, Epidemiology, and End Results (SEER) database were reviewed to analyze cases of pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…PSC exhibits a high mutation level ( 6 , 7 ) compared to other NSCLC subtypes ( 36 , 37 ) ( Figure 1 ). In their study, Schrock et al reported that the mean tumor mutational burden (TMB) of PSC of 13.6 mutations per megabase (Mb), with 20% of cases having a TMB of >20 mutations/Mb and 43% having a TMB of >10 mutations/Mb ( 38 ).…”
Section: Biology Of Pscmentioning
confidence: 99%
See 1 more Smart Citation
“…PSC exhibits a high mutation level ( 6 , 7 ) compared to other NSCLC subtypes ( 36 , 37 ) ( Figure 1 ). In their study, Schrock et al reported that the mean tumor mutational burden (TMB) of PSC of 13.6 mutations per megabase (Mb), with 20% of cases having a TMB of >20 mutations/Mb and 43% having a TMB of >10 mutations/Mb ( 38 ).…”
Section: Biology Of Pscmentioning
confidence: 99%
“…The most frequent mutations in PSC are tumor protein 53 ( TP53 ), Kirsten rat sarcoma viral oncogene homolog ( KRAS ), epidermal growth factor receptor ( EGFR ), and mesenchymal to epithelial transition factor ( MET ) ( 7 , 8 , 17 , 36 - 38 , 41 - 44 ). Yang et al performed comprehensive WES of 56 patients with PSC ( 8 ).…”
Section: Biology Of Pscmentioning
confidence: 99%